Multilinear Commutators of Sublinear Operators on Triebel-Lizorkin Spaces (Communications in Mathematical Research, 2021)
In this paper, the boundedness of multilinear commutators related tosublinear operators with Lipschitz function on Triebel-Lizorkin spaces is given. Asan application, we prove that the multilinear commutators of Littlewood-Paley operator and Bochner-Riesz operator are bounded on Triebel-Lizorkin spaces.